Mysteries of consciousness - Tabanli, Mustafa (New Jersey : Everest Production, 2009)
Considered to be truly the final frontier, why is human consciousness so difficult for us to understand? Why is the source of consciousness so difficult for us to identify? Has our understanding of consciousness deepened since we have employed new techniques and technologies to explore the human brain? In this program we are joined by some of the most fascinating thinkers today who are probing the mysteries of consciousness.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi
DVD format
Keywords: Consciousness; Mind and body; Conscience